Melatonin Hormone Acts on Cells of Maternal Blood and Placenta From Diabetic Mothers - Louis, Martino B. Pierre; França, Danielle Cristina Honorio; Queiroz, Adriele Athaídes; Calderon, Iracema de Mattos Paranhos; França, Eduardo Luzía; Honorio-França, Adenilda Cristina (Frontiers in Physiology, 2022)
Changes in glucose metabolism of diabetic mothers affect immunological components, proinflammatory factors, and placental hypervascularization that can induce cell death. The hormone melatonin has been identified as a potential modulating agent. The aim of this study was to analyze the oxidative process and the apoptosis in maternal blood and placental cells modulated by melatonin from diabetic mothers. The groups were 40 pregnant women divided into non-diabetic (ND) and type 2 diabetes mellitus (T2DM) groups. Blood and placental cells were obtained by density gradient and maintained in culture treated or not with melatonin (100 ng/mL) for 24 hours (37oC, 5% CO2). Oxidative stress was evaluated by superoxide release and CuZn superoxide dismutase (SOD). Apoptosis was assessed by flow cytometry. Maternal hyperglycemia increased superoxide release and apoptosis in MN cells from maternal blood and reduced SOD level and SOD/O2- ratio. Melatonin reduced oxidative stress and apoptosis rates in MN cells in the blood of diabetic mothers. There was a reduction in SOD and SOD/O2- ratio in the placental extravillous layer, and melatonin restored the concentrations of this enzyme. There was greater superoxide release, reduced SOD/O2- ratio, and apoptosis in MN cells placental villous layer. Melatonin increased apoptosis rates in the placental villous layer from hyperglycemic mothers. These data suggest that hyperglycemia altered the processes oxidative in blood and placenta from hyperglycemic mothers. These changes reflected in the mechanisms of induction of apoptosis, especially in the vascularized layers of the placenta, and were modulated by melatonin.